A case of successful treatment of complete atrioventricular block complicated by sudden arrhythmic death in an elderly patient with post COVID-19 thrombocytopenia - N. Y. Semigolovskii; S. O. Mazurenko; S. N. Semigolovskii; M. O. Shabalina («REMEDIUM GROUP» Ltd., 2022)
As established today by a number of studies, transferred COVID-19 (even mild) is associated with a high risk of delayed heart damage. Although human coronaviruses are a minor cause of all cases of viral myocarditis, they have been associated with myocarditis in patients of all age groups. Post-COVID-19 myocarditis can be manifested by heart failure, heart rhythm and conduction disorders. A case report of 14-day hospitalization of an 89 y.o. man for a life-threatening myocardial conduction disorder - complete AV block - on the background of a permanent form of Arial fibrillation, accompanied by clinical death of the patient, coagulopathy, nosocomial pneumonia, heart failure and impaired consciousness. During the treatment, which included cardiopulmonary resuscitation, the use of temporary and then permanent pacemaker, antibiotics, levocarnitine, Fondaparinux, blood clot transfusions for profound thrombocytopenia, led to the restoration of heart rhythm and conduction, reduction of heart failure, cure of nosocomial pneumonia and restoration of exercise tolerance. Post- COVID-19 complications are currently still weakly understood and poorly predicted, but their treatment according to the general rules gives positive results. In patients with heparin-induced thrombocytopenia, as in patients with initial thrombocytopenia (including after COVID-19 conditions), it is advisable to use the drug Fondaparinux, which has proven itself in the prevention and treatment of arterial and venous thromboembolism. In the treatment of posthypoxic complications, it is appropriate to use Levocarnitine to correct post-ischemic changes in the myocardium and brain.